Determinants of Food Security among Chepang Households in Chitwan, Nepal - Kunwar, Prem Bahadur; Dhakal, Shiva Chandra (Journal of Agriculture and Forestry University, 2025)
Chepang, a marginalized indigenous community in Nepal, faces significant socio-economic challenges contributing to food insecurity and malnutrition. This study assesses the food security status and its socio-economic determinants at household level of Chepang community in Ichchhakamana Rural Municipality, Kalika Municipality, and Rapti Municipality of Chitwan. A total of 87 samples were selected using purposive and random sampling techniques with 29 from each selected local level. A mixed-methods approach was used, combining quantitative surveys and qualitative methods including household surveys with semi-structured questionnaire, key informant interviews, and focus group discussions. Data were analyzed using descriptive statistics, food consumption scores for assessing food security status and an ordered logistic regression model to quantify food security based on socio-economic determinants. The results reveal that 23% of households experience food insecurity, 59% are in vulnerable position and only 18% are food secure. Family size, household head education level and annual household income contribute positively and significantly to food security. Coping strategies are mainly relying on wild edibles (41.4%) and wage labor (26.4%). The findings underscore the need for targeted interventions addressing education, income diversification, infrastructure development and land rights to enhance resilience in this socio-economically disadvantaged community. Tailored government programs addressing these areas can significantly improve food security among the Chepang community and contribute to sustainable food systems.